Comparative Study On Work Hour Obedience Before And After The Implementation Of Flexitime Policy - Purniawaty purniawaty; Fibria Indriati Dwi Liestiawati (International Journal Labs, 2024)
This research examined the impact of Flexitime policies on employee obedience to work hours, comparing behaviors before and after its implementation at Pusat Kebijakan Sistem Ketahanan Kesehatan dan Sumber Daya Kesehatan (Pusjak SKKDK) or the Center for Health Resilience Systems and Health Resources Policy. Secondary data that included the attendance records from January 2022 to December 2023 of 106 employees who were sampled using the total sampling technique were comprehensively analyzed. The data of this research underwent parametric statistics in the form of paired sample t-test and non-parametric statistics using Wilcoxon signed ranks test. Results from both parametric and non-parametric analyses consistently revealed a significant shift in work hour obedience among employees following the introduction of flexitime, indicating a positive influence of Flexitime on employee work hour obedience. This research underscores the value of flexible work arrangements, suggesting that such system can significantly enhance employee performance and contribute to the attainment of organizational objectives.